Biocompatibility and Efficacy of a Linearly Cross-Linked Sodium Hyaluronic Acid Hydrogel as a Retinal Patch in Rhegmatogenous Retinal Detachment Repairment - Zheng, Chuanzhen; Xi, Hongwei; Wen, Dejia; Ke, Yifeng; Zhang, Xiaomin; Ren, Xinjun; Li, Xiaorong (Frontiers in Bioengineering and Biotechnology, 2022)
To prevent the migration of retinal pigment epithelial (RPE) cells into the vitreous cavity through retinal breaks after the pars plana vitrectomy for the repairment of rhegmatogenous retinal detachment (RRD), sealing retinal breaks with an appropriate material appears to be a logical approach. According to the review of ocular experiments or clinical trials, the manipulation of covering retinal breaks with most adhesives is complex. A commercially available cross-linked sodium hyaluronic acid (HA) hydrogel (Healaflow®) with the injectable property was demonstrated to be a perfect retinal patch in RRD clinical trials by our team. Based on the properties of Healaflow®, a linearly cross-linked sodium HA hydrogel (HA-engineered hydrogel) (Qisheng Biological Preparation Co. Ltd. Shanghai, China) with the injectable property was designed, whose both cross-linker and cross-linking method was improved. The purpose of this study is to report the characteristics of HA-engineered hydrogel using Healaflow® as a reference, and the biocompatibility and efficacy of HA-engineered hydrogel as a retinal patch in the rabbit RRD model. The HA-engineered hydrogel exhibited similar dynamic viscosity and cohesiveness and G’ compared with Healaflow®. The G’ of HA-engineered hydrogel varied from 80 to 160 Pa at 2 % strain under 25℃, and remained constantly higher than G’’ over the range of frequency from 0.1 to 10 Hz. In the animal experiment, clinical examinations, electroretinograms, and histology suggested no adverse effects of HA-engineered hydrogel on retinal function and morphology, confirming its favorable biocompatibility. Simultaneously, our results demonstrated the efficacy of HA-engineered hydrogel as the retinal patch in the RRD model of rabbit eyes, which can aid in the complete reattachment of the retina without the need for expansile gas or silicone oil endotamponade. The HA-engineered hydrogel could play the role of an ophthalmologic sealant via its high viscosity and cohesivity. This pilot study of a small series of RRD models with a short-term follow-up provides preliminary evidence to support the favorable biocompatibility and efficacy of HA-engineered hydrogel as a promising retinal patch for sealing retinal breaks in retinal detachment repairment. More cases and longer follow-up studies are needed to assess its safety and long-term effect.